Sepi Ing Pamrih dan Wuwei: Kearifan Budaya Jawa dan Tionghoa - Budianto, Pauw (Zenit, 2013)
Both Javanese culture and Chinese culture have a long history and  richness of profound thoughts concerning human beings, socially and cosmologically. Both cultures’ traditional world view have plenty of similarities, especially in the process of cultivation of human’s spiritual dimension to gain the ultimate consciousness, which in Javanese culture is called manunggaling kawula Gusti and in Chinese culture Tian-ren heyi. The process of finding the ultimate  consciousness  needs a specific mind state, called sepi ing pamrih in Javanese culture and wuwei in Chinese culture, and for which a life long gradual process is needed.          Keywords: Javanese culture, Chinese culture, mind state, sepi ing pamrih, wuwei